Statistical Performance and Graphical Analysis of Branding Website User at PT. Reksa Nusindo Sejahtera by Using Google Console and Google Analytics - Afdallah, Daffa Ikhsan; Ayuningsih, Ekatri; Ibrahim (Cattleya Darmaya Fortuna, 2021)
The rapid of information and competition in the world of the internet has caused the website reksanusindosejahtera.com disappear on the first page of Google Search Results and queries. Therefore, it has less viewers and subscribers. Search Egine Optimization (SEO) is a method that will be used to overcome the issue of viewers and subscribers on a website. This research applies Search Engine Optimization (SEO) by using two tools, Google Console and Google Analytics, to optimize keyword searches. The aim of this research is to assist the website in appearing on the first page of Google Search results, thereby maximizing business outcomes. The results of website optimization are based on the analysis and implementation of this method; the main page of the website with the primary keyword reksanusindo.com has been indexed by search engines and appears on the first page of Google search results. It can be confirmed that the statistics for website visits have increased than the previous numbers. Furthermore, this website will continue to be optimized to achieve even better results.